ANALISIS PEMBELAJARAN INKLUSIF PADA ANAK BERKEBUTUHAN KHUSUS TUNARUNGU DI SD MUZDALIFAH MEDAN AMPLAS - Yulia Dewi; Riska Handayani; Anisa Putri; Nabila Balkis Rangkuti; Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe teachers’ efforts in implementing inclusive learning for deaf students in elementary schools. This study employed a descriptive qualitative approach, with data collected through observation and interviews. The results showed that teachers had implemented various strategies to support the learning process of deaf students, such as the use of visual media, simple communication through gestures and written instructions, and individualized guidance. In addition, teachers also applied differentiated learning and encouraged social interaction between deaf students and other students in the classroom. However, the implementation of inclusive learning still faces several challenges, including teachers’ limited ability in using sign language, lack of training in inclusive education, and insufficient supporting learning facilities.